KAJIAN YURIDIS TERHADAP KENDALA SERTA AKIBAT HUKUM DALAM PEMBUATAN DAN PENYIMPANAN SURAT WASIAT (TESTAMEN) BAGI NOTARIS - Arya Lanang, I Gusti Putu; Sukeni, Ni Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013, 2013)
Before the death of a man feel like to give happiness to his descendants, one way to provide legacy, inheritance can be given either directly or through a will. A will made by a testator to his descendants through a notary, Testament must be made by a notary. it is listed in Subparagraph 1 of Article 1 of Law No. 30 Notary of 2004, which states that the notary is a public official authorized to make an authentic deed and other authorities referred to in the Act. In making Testament there are several obstacles that people are going to make a will must be at least 18 years of age or married although not yet 18 years old and who left to have a healthy mind, if the making of the will does not meet the requirements will be null and void law. Notaries to keep and maintain the confidentiality of wills, legal consequences of the notary who does not perform his duty as storage is a testament deed made or kept by a notary deed under hand by law or deed is null and void and a notary to make or save a will be sanctions in the form of a written reprimand, suspension, dismissal with respect, or dismissal with disgrace.
Keywords: Constraint, a Result of the Law, Storage a Notary, and Testament